Self-Efficacy, Reward, and Punishment in Determining Employee Performance: Keyakinan Diri, Imbalan, dan Hukuman dalam Menentukan Kinerja Karyawan - Rojiyah, Dewi; Sumartik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Business competition today demands companies to strengthen human resource performance as a key driver of organizational success. Specific Background: Franchise businesses, such as Pok Pok My Crispy Snack, require optimal employee performance to maintain service quality and operational consistency across branches. Knowledge Gap: Previous studies have discussed performance determinants, but few have jointly examined self-efficacy, reward, and punishment within the context of a growing franchise business. Aims: This study investigates the relationship among self-efficacy, reward, and punishment toward employee performance using a quantitative associative approach with 60 respondents. Results: The findings show that self-efficacy and punishment significantly relate to employee performance, while reward shows no significant relationship. Simultaneously, all three variables are jointly associated with employee performance. Novelty: This study provides empirical evidence that psychological belief and disciplinary mechanisms are stronger predictors of performance than material rewards in small-scale franchise enterprises. Implications: Managers should strengthen employee self-belief and implement fair disciplinary systems to sustain consistent performance and competitiveness in franchise settings. Highlights: Self-efficacy and punishment strongly relate to performance. Reward shows no significant relationship. Franchise context strengthens managerial implications. Keywords: Self-Efficacy, Reward, Punishment, Employee Performance, Franchise Business